Limitations of ethical reasoning as an action (praxis) strategy - Nielsen, Richard P. (Journal of business ethics, 1988)
For both philosophers and managers, reasoning with ourselves and others can be used both as (1) a way of knowing what is ethical and (2) a way of acting to help ourselves, others and organizations behave ethically. However, for many of us, knowing is frequently not the same as acting. Four areas are addressed: (1) thirteen limitations of ethical reasoning as an action strategy; (2) how a better understanding of these limitations can strengthen ethical reasoning as an action strategy; (3) how an understanding of these limitations can serve as a conceptual foundation for exploring other ethical action strategies; and, (4) implications for experiential learning and teaching.